Treatment of relapsed and refractory Waldenstrom Macroglobulinemia. Issue 1 (2nd January 2023) - Amaador, Karima; Kersten, Marie J.; Minnema, Monique C.; Vos, Josephine M. I.
Abstract: Waldenström's Macroglobulinemia (WM) is a rare type of indolent non-Hodgkin lymphoma (NHL) that remains incurable. Several effective agents such as monoclonal antibodies (in combination with chemotherapy), Bruton's tyrosine kinase inhibitors, proteasome inhibitors, and BCL2 inhibitors are (becoming) available for the treatment of relapsed and refractory WM. There is however no consensus on a preferred treatment in the relapsed setting. Choice of therapy in relapsed WM should be individualized by taking several treatment and patients characteristics into account, such as treatment duration, toxicity, age, comorbidities and MYD88 L265P and CXCR4 mutational status. Due to better understanding of WM biology and the arrival of novel anti-lymphoma agents, the therapeutic options are increasing. Non-cytotoxic and fixed duration regimens, such as those explored in other indolent NHLs should be the focus of future clinical trials in WM.